Factors Predicting the Axillary Lymph Node Metastasis in Breast Cancer: Is Axillary Node Clearance Indicated in Every Breast Cancer Patient?: Factors Predicting the Axillary Lymphnode Metastases in Breast Cancer - Ashturkar, Amrut V. (Springer-Verlag, 2011)
The study was carried out to find out predictors of axillary lymph node metastasis in breast cancer and to evaluate its significance in selecting the group of patients in whom axillary dissection could be avoided. Ninety-five breast cancer patients who underwent mastectomy and axillary dissection were included in the study. Factors like patient’s age, tumor size, histopathological type, histological grade and estrogen and progesterone receptor status were correlated with the axillary metastases. Out of 95 cases axillary metastasis was found in 47 (49.47%) cases. There was no correlation between patient’s age and tumor size with axillary metastasis (p > 0.05). Based on histopathological typing tumors like ductal carcinoma in situ, tubular carcinoma and mucinous carcinoma showed less tendency for axillary metastasis (p < 0.046). Association was found between histological grade and estrogen receptor and progesterone receptor positivity with presence of axillary metastasis (p < 0.001 and 0.002 respectively). The findings in this study indicate that breast cancer patients having favorable histological type, grade I tumors and estrogen and progesterone receptor negative tumor are good candidates to avoid axillary dissection.